2023
DOI: 10.3390/s23218795
|View full text |Cite
|
Sign up to set email alerts
|

Path Planning of a Mobile Delivery Robot Operating in a Multi-Story Building Based on a Predefined Navigation Tree

Jordi Palacín,
Elena Rubies,
Ricard Bitriá
et al.

Abstract: Planning the path of a mobile robot that must transport and deliver small packages inside a multi-story building is a problem that requires a combination of spatial and operational information, such as the location of origin and destination points and how to interact with elevators. This paper presents a solution to this problem, which has been formulated under the following assumptions: (1) the map of the building’s floors is available; (2) the position of all origin and destination points is known; (3) the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 125 publications
0
3
0
Order By: Relevance
“…The granularity of the grid and the connectivity of the nodes define the computational challenge that represents the use of deterministic search algorithms [60] to plan the trajectory of the robot. However, recent works have demonstrated that similar navigation results can be obtained when using a navigation tree that is not based on a discrete grid definition [61].…”
Section: Methods For 2d Map Creationmentioning
confidence: 82%
See 1 more Smart Citation
“…The granularity of the grid and the connectivity of the nodes define the computational challenge that represents the use of deterministic search algorithms [60] to plan the trajectory of the robot. However, recent works have demonstrated that similar navigation results can be obtained when using a navigation tree that is not based on a discrete grid definition [61].…”
Section: Methods For 2d Map Creationmentioning
confidence: 82%
“…The main differential elements of the proposed robot are its size (1.76 m, 30 kg), its human interaction capability [52], and its omnidirectional mobility [50]. The robot also has the ability to navigate between the floors of a multi-story building [61]. A series of experiments were conducted in an educational building to measure the CO 2 levels in different classrooms with the robot.…”
Section: Discussionmentioning
confidence: 99%
“…Food delivery will increasingly be carried out using automated vehicles, such as small robot vehicles or drones. , Further research is therefore required to develop the hardware and software required to operate these automated vehicles to make they affordable, reliable, and robust while also ensuring food quality and safety.…”
Section: Miscellaneous Areasmentioning
confidence: 99%